Post-Covid city: what are we talking about? - Rodríguez-Barcón, Alberto (2021)
As the pandemic progresses towards all corners of the globe, it becomes more noticeable how this crisis is undermining some of the central aspects that give meaning to urban life. In this scenario, future urban planning must learn to implement city models capable of responding to this kind of challenge. The constant reflections that appear regularly coincide in pointing out that COVID-19 has disrupted the dynamics of the contemporary city unveiling significant weaknesses in terms of management, social cohesion, and planning. From this evidence, scholars argue that a new model of the city will emerge once we overcome this crisis. But what kind of city? Through a literature review this paper identifies four central areas that underpin the construction of the new Post-COVID city, urging for a global and multidisciplinary debate and joint reflection on the opportunities that open in this context of global crisis.